Targeting nanoparticle-conjugated microbubbles combined with ultrasound-mediated microbubble destruction for enhanced tumor therapy. (December 2022) - Chen, Kuo-Wei; Hsu, Po-Hung; Huang, Hau-Lun; Liu, Hao-Li; Lin, Ya-Tin; Hsu, Che-Yu; Lin, Jui-Hsiang; Lin, Yu-Hsin
Abstract: The stress of the abnormal stromal matrix of solid tumors is a major limiting factor that prevents drug penetration. Controlled, accurate, and efficient delivery of theranostic agents into tumor cells is crucial. Combining ultrasound with nanocarrierbased drug delivery systems have become a promising approach for targeted drug delivery in preclinical cancer therapy. In this study, to ensure effective tumor barrier penetration, access to the tumor microenvironment, and local drug release, we designed targeted nanoparticle (NP)-conjugated microbubbles (MBs); ultrasound could then help deliver acoustic energy to release the NPs from the MBs. The ultrasound-targeted MB destruction (UTMD) system of negatively charged NPs was conjugated with positively charged MBs using an ionic gelation method. We demonstrated the transfer of targeted NPs and their entry into gastric cancer cells through ligand-specific recognition, followed by enhanced cell growth inhibition owing to drug delivery-induced apoptosis. Moreover, the UTMD system combining therapeutic and ultrasound image properties can effectively target gastric cancer, thus significantly enhancing antitumor activity, as evident by tumor localization in an orthotopic mouse model of gastric cancer. The combination of ultrasound and NP-based drug delivery systems has become a promising approach for targeted drug delivery in preclinical cancer therapy. Graphical Abstract: The ultrasound-targeted microbubble (MB) destruction (UTMD) system of negatively charged nanoparticle (NP) was conjugated with positively charged MBs using an ionic gelation method. The UTMD system combining therapeutic and ultrasound image properties can effectively target gastric cancer, thus significantly enhancing antitumor activity, as evident by tumor localization in an orthotopic mouse model of gastric cancer. ga1